Franklin's bad day - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic, 1997)
When Franklin the turtle's best friend Otter moves away it makes him feel sad, grumpy, and a little bit mean, but Franklin cheers up after sharing a heart-to-talk and a hug with his dad.
2.8
K-3
Keywords: Emotions -- Fiction; Turtles -- Fiction; Emotions -- Fiction; Turtles -- Fiction